Materialities in and of Institutional Care for Elderly People - Artner, Lucia (Frontiers in Sociology, 2018)
Since some decades, nursing homes for elderly people are discussed as “total institutions” in the sense of Erving Goffman. However, this line of research has not clarified yet as to how the creation of a totalizing nursing home is actually achieved on the basis of everyday practices and interactions. In my contribution I address this research gap by looking at how material and spatial arrangements in nursing homes for elderly people affect the ways its residents are socially constructed. By drawing on Goffman’s ideas on the creation and presentation of the self, I engage with the question of how the placement and handling of material objects in nursing interactions lead to the institutionalization of a resident’s self: Empirical examples of how materialities are deployed demonstrate how residents are stripped of their self identity and how nursing staff members exercise rigid control over their everyday lives. Yet, it is also shown how the usage of material objects help residents to subvert some of these practices. I argue that looking at the material and spatial arrangements of a nursing home on a micro-level of social interactions helps us especially in reconstructing those often latent, inconspicuous and overseen processes in which a totalizing environment is created.